Pengaruh Modal Intelektual, Rasio Utang, Ukuran Perusahaan dan Pertumbuhan Perusahaan terhadap Nilai Perusahaan - Meily Juliani; Saphira Evani (Jurnal Akuntansi, 2022)
This research intends to analyze the effects of intellectual capital, debt ratio, firm size and firm growth on firm value in Indonesia. The research sample comprised 143 manufacturing firms listed on the Indonesia Stock Exchange (IDX) from the year 2017 through year 2021. The data analysis approaches used are descriptive statistical analysis and panel data analysis. Hypothesis test results indicate that intellectual capital and firm size have a significant positive effect on firm value, the debt ratio has a significant negative effect on firm value and firm growth has no significant effect on firm value.Keywords: Firm Value, Intellectual Capital, Debt Ratio, Firm Size, and Firm Growth